Safety and effectiveness of outpatient laparoscopic cholecystectomy in a teaching hospital: a prospective study of 110 consecutive patients - Marinis, Athanasios (BioMed Central, 2010)
BACKGROUND: The aim of this study was to evaluate the safety and efficacy of outpatient laparoscopic cholecystectomy (OLC) in a day surgery unit in a teaching hospital. OLC was offered to patients with symptomatic cholelithiasis who met the following established inclusion criteria: ASA (American Society of Anesthesiology) physical status classification class I and II; age: 18 - 70 years; body mass index (BMI) < 30 kg/m(2); patient acceptance and cooperation (informed consent); presence of a responsible adult to accompany the patient to his residency; patient residency in Athens. The primary study end-point was to evaluate success rates (patient discharge on the day of surgery), postoperative outcome (complications, re-admissions, morbidity and mortality) and patient satisfaction. A secondary endpoint was to evaluate its safe performance under appropriate supervision by higher surgical trainees (HSTs). FINDINGS: 110 consecutive patients, predominantly female (71%) and ASA I (89%) with a mean age 40.6 ± 8.1 years underwent an OLC. Surgery was performed by a HST in 90 patients (81.8%). A mean postoperative pain score 3.3 (range 0-6) occurred in the majority of patients and no patient presented postoperative nausea or vomiting. Discharge on the day of surgery occurred in 95 cases (86%), while an overnight admission was required for 15 patients (14%). Re-admission following hospital discharge was necessary for 2 patients (1.8%) on day 2, due to persistent pain in the umbilical trocar site. The overall rate of major (trocar site bleeding) and minor morbidity was 15.5% (17 patients). At 1 week follow-up, 94 patients (85%) were satisfied with their experience undergoing OLC, with no difference between grades of operating surgeons. CONCLUSIONS: This study confirmed that OLC is clinical effective and can be performed safely in a teaching hospital by supervised HSTs.